Adsorption of Methyl Violet 2B Dye by Silica from Glass Bottle Waste - Ni’mah, Yatim Lailun; Faqih, Muhammad Zidan Chisa; Suprapto, Suprapto; Yuningsih, Nabila Eka; Jamari, Nor Laili-Azua (Universitas Gadjah Mada, 2026)
In this study, silica gel was successfully synthesized using waste from chemical reagent glass bottles. The synthesized silica gel was then tested for its effectiveness in adsorbing methyl violet 2B dye. To optimize the adsorption process, Surface Response Methodology (RSM) was employed, utilizing the Box-Behnken design (BBD) for factor and input design. Characterization of the synthesized silica gel through XRD analysis revealed an amorphous structure and mesoporous pores, with a purity of 75.63%. The optimization process focused on four key factors: pH (3 to 9), initial concentration of methyl violet 2B (10 to 30 mg/L), adsorbent mass (30 to 100 mg), and contact time (15 to 60 min). The optimal conditions for adsorbing methyl violet 2B were determined to be a pH range of 7–9, an initial methyl violet 2B concentration of 27–30 mg/L, an adsorbent mass of 70–95 mg, and a contact time of 30–40 min. Under these optimized conditions, the methyl violet 2B removal efficiency of 98.69% was achieved. Further analysis indicated that the adsorption of methyl violet 2B onto the synthesized silica gel followed the Temkin isotherm and pseudo-second-order kinetics models.